2013
DOI: 10.1378/chest.12-1205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 21-Gauge and 22-Gauge Aspiration Needle in Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration

Abstract: Lung cancer is the third most commonly diagnosed cancer and accounts for the greatest number of cancer-related deaths in the United States. 1 The majority of patients with lung cancer present with advanced stage disease and will not benefi t from surgical resection. It is imperative to obtain mediastinal lymphatic tissue sampling in order to stage the mediastinum to prevent patients with advanced disease Results: A total of 1,235 patients met inclusion criteria. Sample adequacy was obtained in 94.9% of the 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Two retrospective studies [11,12] had similar results, also failing to find a difference in the overall diagnostic yield between EBUS-TBNA using 22- and 21-gauge needles. The study by Yarmus et al [11] analyzed data from the AQuIRE (American College of Chest Physicians Quality Improvement Registry, Evaluation and Education) Data Registry with multicenter contributions; 249 procedures were performed with 21-gauge needles, and 995 were performed with 22-gauge needles.…”
Section: Results Of Pico Questionmentioning
confidence: 83%
See 1 more Smart Citation
“…Two retrospective studies [11,12] had similar results, also failing to find a difference in the overall diagnostic yield between EBUS-TBNA using 22- and 21-gauge needles. The study by Yarmus et al [11] analyzed data from the AQuIRE (American College of Chest Physicians Quality Improvement Registry, Evaluation and Education) Data Registry with multicenter contributions; 249 procedures were performed with 21-gauge needles, and 995 were performed with 22-gauge needles.…”
Section: Results Of Pico Questionmentioning
confidence: 83%
“…The study by Yarmus et al [11] analyzed data from the AQuIRE (American College of Chest Physicians Quality Improvement Registry, Evaluation and Education) Data Registry with multicenter contributions; 249 procedures were performed with 21-gauge needles, and 995 were performed with 22-gauge needles. No differences in either sample adequacy (per LN analysis) or diagnostic yield (both per patient and per LN analysis) were found.…”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…The impact of aspiration needles on specimen adequacy or diagnostic yield during EBUS-TBNA has not been well studied and the findings are controversial. Yarmus et al [9] evaluated the diagnostic yield of the needle gauge in 1,299 patients who underwent EBUS-TBNA. Their work revealed no difference in specimen adequacy or diagnostic yield by using different needle gauges (21 vs. 22 G).…”
Section: Discussionmentioning
confidence: 99%
“…In one of the largest EBUS‐TBNA studies reported to date, sample adequacy was 90% and diagnostic yield ranged from 37% to 54% depending on hospital volume . While not as well studied in pediatrics, EBUS‐TBNA has become well accepted for the evaluation of lymphadenopathy unrelated to primary lung cancer, such as lymphoma and sarcoidosis …”
Section: Discussionmentioning
confidence: 99%